A New Approach to Analysis of Inverter Currents - Pekik Argo Dahono (Institute for Research and Community Services (LPPM) ITB, 1998)
In this paper, a new approach to analysis of the average and rms currents in inverter switching devices and the rms value of the ripple component of inverter input current is presented. The proposed approach is based on the probability with which the inverter switching devices receive ON signals which can be obtained from the average value of the phase-to-dc midpoint voltages. As the knowledge of the exact switching pattern is not required, this approach is especially useful for inverters in which the exact switching patterns can not be predetermined. To show the general applicability of the proposed approach, the expressions for the average and rms currents in switching devices and the rms value of the ripple component of input current of three-phase hysteresis current-controlled and PWM inverters are derived. Experimental results are included to show the validity of the proposed method. Suatu Pendekatan Baru untuk Analisis Arus-arus InverterDalam makalah ini dipresentasikan, suatu pendekatan baru umtuk analisis arus rata-rata dan rms pada komponen-komponen switching inverter dan nilai rms riak arus masukan inverter. Pendekatan yang diusulkan berbasis pada peluang komponen-komponen switching inverter menerima sinyal ON yang didapatkan dari nilai rata-rata tegangan fasa keluaran. Karena pengetahuan detil tentang pola switching inverter tidak diperlukan, metoda yang diusulkan sangat cocok untuk analisis arus-arus pada inverter dengan pola switching yang tidak bisa ditentukan. Untuk menunjukkan luasnya daerah penerapan, persamaan-persamaan arus rata-rata dan rms komponen switching dan nilai rms riak arus masukan dari inverter yang menggunakan pengendali arus jenis hysteresis dan yang menggunakan pengendali PWM diturunkan. Hasil pengukuran disertakan untuk menunjukkan validitas metoda yang diusulkan.